StoryJumper as a Learning Medium: Integrating Technology in Kampung Inggris Transmigrasi Kalimantan Selatan - Amelia, Rizky; Salman, Putriana; Heldiansyah, Heldiansyah; Ardida, Shintia Dewi Aprilia; Rahman, Lutfy; Nurmaya, Reni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This article explores the integration of StoryJumper, a digital storytelling platform, into English language instruction in Kampung Inggris Transmigrasi, South Kalimantan. Through a community service program, ten English tutors received training on creating StoryJumper content to enhance student engagement. Pre- and post-tests were given to participants. The results of the analyses indicated positive perceptions towards technology use in education, with participants recognizing its potential to foster student-centered learning to boost their learning motivation. However, technical challenges highlighted the need for additional support. The results suggest that digital storytelling can be a powerful educational tool in the classroom and out-of-class activities. This initiative could serve as a model for similar community-driven programs in other transmigration areas, promoting educational quality for every student.